(untitled) (TROPICAL WETLAND JOURNAL, 2024)
Meat is an important food commodity in meeting nutritional needs. Damage that leads to a decrease in the quality of fresh meat is mainly caused by microorganisms. One of the pathogenic bacteria that can contaminate broiler meat is Salmonella sp. This research aims to determine the food safety level of broiler meat sold in traditional markets in the city of Banjarbaru regarding contamination by Salmonella sp. bacteria and to prevent the circulation of poultry-origin products (broilers) that do not meet the required standards, which can threaten consumer health. The research method used in this study is a survey and laboratory analysis. This study utilized 56 chicken meat samples from 4 traditional markets using a random sampling method. The test results showed that 18 samples were contaminated with Salmonella sp. bacteria out of the 56 samples. This indicates that the quality of chicken meat sold in some traditional markets, 32.14%, does not meet the standards based on the Indonesian National Standard for chicken meat (SNI 7388:2009)